PENGARUH RETURN ON ASSET DAN ARUS KAS UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS: (Studi Kasus Pada Perusahaan Go Public Manufaktur Sektor Industri Kimia Dasar Periode 2009-2013) - Fatahillah Fatahillah; Fitriya Sari (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2017)
This study aimed to examine the effect of the Return On Asset (ROA) and the cash flow for prediction of financial distress in the company go public manufacturing basic chemical industry sector. This study was a descriptive study with a quantitative approach. Samples are six publicly traded companies included in the basic chemical industry sub-sector with the study period 2009-2013. The six companies are PT. Asahimas Flat Glass Tbk, PT. Arwana Citra Mulia Tbk, PT. Ceramic core Alamasri Industry Tbk, PT. Assosiasi Keramika Indonesia Tbk, PT. Industrindo Mulia Tbk and PT. Surya Toto Indonesia Tbk. This study uses secondary data obtained from the annual financial statements published by the company on the Indonesian Stock Exchange website. Data analysis technique used by logistic regression. The results of this study prove that the ROA and cash flow have a significant effect in predicting the company'sfinancial distress. The information value of profit after tax (EAT) has the ability to predict financial distress in a company. This is demonstrated by the significant values are under 0.05. The information value of cash flow (CF) has no significant effect. It is seen from the logistic regression test value of 0.938 which means that cash flow information does not have the ability to predict financial distress of a company.